The Effect Of Progressive Muscle Relaxation Technique (PMRT) On The Quality Of Life Of Third Trimester Pregnant Women At Public Health Centre II, West Denpasar District - Ni Gusti Ayu Pramita Aswitami; I Gusti Gede Mayun Surya Darma; Ni Made Septiari Maryani Ardi (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Pregnancy impacts a women’s physical and mental state. These modifications will have an impact on pregnant women’s quality of life. Pregnant women’s poor quality of life will impact the fetus and mother’s health. As a result, nonpharmacological therapy, such as the use of progressive muscle relaxation techniques (PMRT), is required to improve the quality of life of pregnant women. PMRT research has so far been linked to anxiety and depression in pregnant women that it is still limited in its application to the quality of life of pregnant women in the third trimester. This study aims to see how beneficial PMRT is in improving the quality of life of pregnant women. A quasi-experimental approach with a pre-post test with Nonequivalent Control Groups is used in this investigation. With a total sample size of 46 participants, non-probability sampling was used to pick the sample. Questionnaires are used to collect data, and t-independent analysis is used to analyze it. There were p-value 0.05 variations in the quality of life of pregnant women in the control and treatment groups after receiving PMRT. The average improvement in quality of life in the control and treatment groups was significantly different (p-value 0.05). For each dimension, there was a significant difference in the quality of life between the control and intervention groups before and after the research (p-value). It is expected that health workers will provide PMRT in pregnancy health services to improve the quality of life of pregnant women.